Dari Keaslian Merek Ke Loyalitas Merek: Peran Mediasi Emotional Attachment Pada Pengguna FOOM (Studi pada Mahasiswa S1 FISIP Universitas Sumatera Utara) - Maria Angela Sijabat; Amelia Gabriel Simangunsong; Anggreana Ongga; Daniel Fritz Weber Sinaga; Meli Oktaviani Tafonao; Onan Marakali Siregar; Ummi Salamah Sitorus (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The growth of the electric cigarette (vape) industry in Indonesia has transformed vape from merely an alternative smoking product into part of a modern lifestyle, especially among young consumers. In an increasingly competitive market, brand loyalty is no longer formed solely through functional product value, but also through emotional relationships between consumers and brands. This study aims to analyze the effect of brand authenticity on emotional attachment and brand loyalty, as well as to examine the mediating role of emotional attachment in the relationship between brand authenticity and brand loyalty among FOOM users at the Faculty of Social and Political Sciences, Universitas Sumatera Utara. This study employed a quantitative associative approach involving 100 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using SEM-PLS with SmartPLS software. The findings indicate that brand authenticity has a positive and significant effect on emotional attachment (H1 accepted). Emotional attachment also has a strong positive effect on brand loyalty (H2 accepted). However, the direct effect of brand authenticity on brand loyalty was not significant (H3 rejected, p = 0.129 > 0.05), indicating full mediation by emotional attachment (H4 accepted). The R² value of brand loyalty was 0.833, indicating that brand authenticity and emotional attachment explain 83.3% of the variance in brand loyalty. These findings suggest that brand loyalty among FOOM users is not formed directly through perceptions of brand authenticity, but through the development of strong emotional attachment toward the brand.